Pelatihan Kerja, Dukungan Organisasi, dan Kinerja Karyawan: Peran Mediasi Motivasi Kerja pada Ritel Modern di Indonesia - Sutriningsih, Titik; Hakim, Lukman Nuzul (GEMA : Jurnal Gentiaras Manajemen dan Akuntansi, 2025)
This study aims to analyze the influence of job training and organizational support on employee performance, with work motivation serving as an intervening variable at PT Sumber Alfaria Trijaya Tbk, Lampung Branch. Employing a quantitative associative approach through a survey method and purposive sampling technique, the research involved 200 respondents who had been employed for at least one year. Data were collected using a Likert-scale questionnaire and analyzed through validity and reliability tests, classical assumption tests, and path analysis using SPSS version 26. The findings reveal that job training and organizational support significantly influence both work motivation and employee performance, either directly or indirectly through motivation as a mediating variable. The R² value of 0.487 for work motivation and 0.533 for employee performance indicates that the model has a strong explanatory power. These results highlight the critical role of work motivation in enhancing the effects of training and organizational support on performance and suggest that organizations should design more integrated and sustainable human resource development strategies. This study offers novelty by integrating work motivation as a mediating variable in the relationship between training and organizational support on employee performance in the modern retail sector, which has rarely been examined simultaneously in the context of regional branches. The findings are expected to serve as new empirical evidence for developing motivation-based performance improvement models in the Indonesian retail industry.